PENGARUH PENGGUNAAN METODE SUKU KATA TERHADAP KEMAMPUAN MEMBACA PERMULAAN SISWA KELAS I SDN I PLUMBON - Febiyolah, Dwi; Nurhabibah, Prabawati; Wahyuningsih, Asih (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to determine the effect of the use of the syllable method on the early reading ability of first-grade students of SDN I Plumbon. This study uses a quantitative approach with a pre-experimental design